Elastic Layers to Reduce Sound Transmission in Lightweight Buildings. Issue 1 (March 2013) - Ljunggren, Fredrik; Ågren, Anders
To obtain satisfactory sound insulation is a challenging task when designing lightweight buildings. Poor performance at low frequencies as well as severe flanking transmission has traditionally often been more pronounced compared to heavier constructions. In the present casestudy based paper, various aspects of using elastic layers to improve sound insulation in lightweight buildings are considered. The effect on impact and airborne sound insulation by using two different kinds of vibration insulators between floor plans was examined together with the effect of using glues of various degree of elasticity in the construction. In situ measurements were performed inside a four-storey wooden frame based residential building and statistically significant variations in sound insulation were found. The efficiency of the two vibration insulators was further evaluated by vibration reduction measurements over the junctions. The difference in vibration reduction was found to be nearly constant in the frequency range 50–1000 Hz while the improvement of impact sound insulation increased by frequency. A long term test of elastic glues was also conducted, during three years, for stability over time. The best glues preserved a significantly higher damping ratio over time compared to the main part of the glues.